Relationship Between Loneliness and Social Adjustment of New Students - Gina Damayanti; Taufik Taufik (Universitas Negeri Padang, 2019)
This research is motivated by the phenomenon of the existence of new students who are difficult to deal with new people, difficult to adjust to family, inferior to friends, secure difficulties from friends, and are kept sanctified by friends and warm wishes. This study aims to: (1) describe the solitude of new students, (2) describe the social understanding of new students, and (3) discuss the significant relationship between solitude and social learning of new students. This research is a descriptive correlational type of research with quantitative methods. The population of this research is the new students of S1 FIP UNP 2018/2019 who come from outside West Sumatra. The total sample of 89 students selected by using the Proportional Random Sampling technique. The research instruments used were the lonely questionnaire and the social share questionnaire. Data were analyzed with descriptive statistical techniques and Pearson Product Moment techniques with the help of the SPSS program for Windows 20.0. The results of the study revealed that (1) the solitude of new students in the high category, (2) social discussion of new students in the medium category, and (3) had a significant negative relationship between loneliness and new students' social exchanges of -0,963 at the significance level of 0, 01 Based on the findings of the study, it is suggested to the college counselors to be able to provide guidance and counseling to new students, in order to provide assistance and services that contain guidance and counseling services regarding loneliness and low social conditions.